Analisis Integrasi Nilai Karakter Peduli Lingkungan dan Tanggung Jawab dalam Buku Ajar Kimia SMA - Mauliza Mauliza; Nurhafidhah Nurhafidhah*; Hasby Hasby (Jurnal Pendidikan Sains Indonesia, 2021)
Indonesia is one of the positive countries for the corona virus (Covid-19). Experts cite several reasons for the increasing number of cases, one of which is the attitude of the public who careless about minimizing contact between people, the lack of sanctions for violations of self-quarantine, and the lack of location information that the community must avoid. The attitude of caring society, especially education actors, is certainly one of the important things that needs attention. Environmental care and responsibility are character values that need to be developed. Students can get character education through the learning process and learning resources, one of which is textbooks. The purpose of this study was to determine whether there is an integration of character values and what is the percentage of integration of character values in high school chemistry textbooks that have been used by teachers in learning, especially the character of environmental care and responsibility. This research is a quantitative descriptive study using the questionnaire and observation sheet instruments. The sample in this study is the class X chemistry textbook that is most often used in teaching and learning activities at SMA Negeri 2 and SMA Negeri 4 Langsa City. The results showed that there was an integration of the character values of environmental care and responsibility in the X grade chemistry textbooks used by teachers of SMA Negeri 2 and SMA Negeri 4 Kota Langsa. The integration of environmental care character values is 38%, while the responsibility character values is 63%. The integration of the character values of environmental care and responsibility in the class X chemistry textbook appears in the column project activities, student activities, content content, and evaluation.